2013
DOI: 10.3892/ijo.2013.1993
|View full text |Cite
|
Sign up to set email alerts
|

PDCD5 expression predicts a favorable outcome in patients with hepatocellular carcinoma

Abstract: Liver cancer in men is the fifth most frequently diagnosed cancer worldwide. Programmed cell death 5 (PDCD5) is an apoptosis related gene and plays an important role in the pathogenesis and development of cancer. In this study, we confirmed that the levels of PDCD5 mRNA and protein were lower in hepatocellular carcinoma (HCC) tissue compared to normal tissue. PDCD5 expression was significantly associated with HBV infection, tumor number, lymph node metastasis and the survival time of the patients with HCC. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…In our previous study, we confirmed that the levels of PDCD5 mRNA and protein were lower in HCC tissue than normal tissue (15). In this study, we investigated the potential role of KLF9 in HCC.…”
Section: Introductionsupporting
confidence: 59%
“…In our previous study, we confirmed that the levels of PDCD5 mRNA and protein were lower in HCC tissue than normal tissue (15). In this study, we investigated the potential role of KLF9 in HCC.…”
Section: Introductionsupporting
confidence: 59%
“…Notably, it was observed that rhPDCD5 could induce apoptosis and S phase arrest in HCC cells. Certain previous studies have demonstrated that PDCD5 is not only an apoptotic accelerator but also an apoptotic trigger (6,13). rhPDCD5 has been shown to enter a variety of cells by CIE and exert biological activities (7,8).…”
Section: Discussionmentioning
confidence: 98%
“…Programmed cell death 5 (PDCD5), also designated TF-1 cell apoptosis-related gene-19 (TFAR19), was identified in TF-1 cells undergoing apoptosis (3). Decreased expression of PDCD5 has been characterized in human tumors, including breast cancer (4), gastric cancer (5), and hepatocellular carcinoma (6). Recombinant human PDCD5 (rhPDCD5) has been shown to enter a variety of cells by clathrin-independent endocytosis (CIE) (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased expression of PDCD5 has been reported in various human tumors, such as gastric cancer (Gao et al, 2012), brain tumors (Li et al, 2008), bone tumor (Chen et al, 2010a), ovarian carcinomas (Zhang et al, 2011), leukemia (Ruan et al, 2006, renal tumor (Tan et al, 2006), lung cancer (Spinola et al, 2006), prostate cancer (Du et al, 2009), hepatocellular cancer (Fu et al, 2013), laryngeal cancer (Xu et al, 2013), oral squamous cell carcinoma (Zhao et al, 2013) and cervical cancer . PDCD5 expression predicts a favorable outcome in patients with hepatocellular carcinoma, epithelial ovarian carcinomas, chondrosarcoma.…”
Section: Various Cancersmentioning
confidence: 99%